East Asian contributions to Dutch traditional and western commercial chickens inferred from mtDNA analysis - Dana, N.; Megens, H.-J.; Crooijmans, R.P.M.A.; Hanotte, Olivier H.; Mwacharo, Joram M.; Groenen, M.A.M.; Arendonk, Johan A.M. van (Wiley, 2011)
Understanding the complex origin of domesticated populations is of vital importance for understanding, preserving and exploiting breed genetic diversity. Here, we aim to assess Asian contributions to European traditional breeds and western commercial chickens for mitochondrial genetic diversity. To this end, a 365-bp fragment of the chicken mtDNA D-loop region of 16 Dutch fancy breeds (113 individuals) was surveyed, comprising almost the entire breed diversity of The Netherlands. We also sequenced the same fragment for 160 commercial birds representing all important commercial types from multiple commercial companies that together represent more than 50% of the worldwide commercial value. We identified 20 different haplotypes. The haplotypes clustered into five clades. The commonest clade (E-clade) supposedly originates from the Indian subcontinent. In addition, both in commercial chicken and Dutch fancy breeds, many haplotypes were found with a clear East Asian origin. However, the erratic occurrence of many different East Asian mitochondrial clades indicates that there were many independent instances where breeders used imported exotic chickens for enhancing local breeds. Nucleotide diversity and haplotype diversity analyses showed the influence of the introgression of East Asian chicken on genetic diversity. All populations that had haplotypes of multiple origin displayed high inferred diversity, as opposed to most populations that had only a single mitochondrial haplotype signature. Most fancy breeds were found to have a much lower within-population diversity compared to broilers and layers, although this is not the case for mitochondrial estimates in fancy breeds that have multiple origin haplotypes.